Quality of reporting in abstracts of randomized controlled trials published in leading journals of periodontology and implant dentistry: a survey - Faggion Junior, Clóvis Mariano; Giannakopoulos, Nikolaos Nikitas (Journal of periodontology, 2012)
Background: Most readers, reviewers, and editors rely on abstracts to decide whether to assess the full text of an article. A research abstract should, therefore, be as informative as possible. The standard of reporting in abstracts of randomized controlled trials (RCTs) in periodontology and implant dentistry has not yet been assessed. The objectives of this review are: 1) to assess the quality of reporting in abstracts of RCTs in periodontology and implant dentistry, and 2) to investigate changes in the quality of reporting by comparing samples from different periods. Methods: The authors searched the PubMed electronic database, independently and in duplicate, for abstracts of RCTs published in seven leading journals of periodontology and implant dentistry from 2005 to 2007 and from 2009 to 2011. The quality of reporting in selected abstracts with reference to the CONSORT (Consolidated Standards of Reporting Trials) for Abstracts checklist published in January 2008 was assessed independently and in duplicate. Cohen κ statistic was used to determine the extent of agreement of the reviewers. Pearson χ2 test and/or Fisher exact test were used to assess differences in reporting in the two samples. Level of significance was set at P <0.05. Results: Three hundred ninety-two abstracts are included in this review. Three items (intervention, objective, and conclusions) were almost fully reported in both samples. In contrast, other items (randomization, trial registration, and funding) were never reported. There were significant changes in reporting for only two items, trial design and title (items better reported in the pre- and post-CONSORT samples, respectively). Most topics, however, were similarly poorly reported in both samples of abstracts. Conclusions: The quality of reporting in abstracts of RCTs in periodontology and implant dentistry can be improved. Authors should follow the CONSORT for Abstracts guidelines, and journal editors should promote clear rules to improve authors’ adherence to these guidelines.
Gesehen am 14.11.2018